Strategy for Strengthening Moral Values in Islamic Education Institutions through Exemplary and Habituating Models - Hakim, Lukman; Muiz, Abdul; Prawirosastro, Carlos Lazaro (Pusdikra-Publishing.com, 2025)
Strengthening the moral values of students is the main challenge in Islamic education in the modern era which is full of moral crises and value disruptions. This study aims to analyze the strategy of strengthening moral values in Islamic educational institutions through the model of example and habituation as the main approach in the formation of Islamic character. This study uses a qualitative approach with a case study design in two Islamic educational institutions in Central Java, involving ten key informants consisting of school principals, PAI teachers, and students. Data collection techniques are carried out through participatory observation, in-depth interviews, and documentation, while data analysis is carried out thematically through data reduction, data presentation, and conclusion drawn. The results of the study show that the exemplary model shown by educators in the aspects of attitudes, speech, and daily behavior is able to form a positive culture in the school environment, while the habituation of moral values such as discipline, responsibility, and honesty is carried out through daily routine activities, strengthening religious programs, and integrating values in the curriculum. The conclusion of this study emphasizes that the strategy of exemplary and habituation is an effective and sustainable approach in shaping the moral character of students, and makes an important contribution to the development of a holistic and contextual Islamic education model.